2014
DOI: 10.1002/gps.4241
|View full text |Cite
|
Sign up to set email alerts
|

The relation between social network site usage and loneliness and mental health in community‐dwelling older adults

Abstract: In this sample, which was representative for the Dutch population, social network sites usage was unrelated to loneliness and/or mental health. The results indicate that a simple association between social network site usage and loneliness and mental health as such, cannot automatically be assumed in community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 25 publications
2
81
1
1
Order By: Relevance
“…Evidence for the relationship between SNS use and loneliness was mixed, with two studies finding no evidence for a simple association between SNS use and loneliness (Aarts, Peek and Wouters 2014;Bell et al 2013), and one study with an experimental design finding no change in loneliness following an SNS intervention (Myhre et al 2016). A qualitative study indicated that participants felt less lonely following an SNS intervention (Ballantyne et al 2010) and one study suggested that SNS use reduced the impact of functional disability on 'social' loneliness (frequency of social contact) (van Ingen, Rains and Wright 2017).…”
Section: What Is the Association Between Sns Use And Older Adults' Wementioning
confidence: 99%
“…Evidence for the relationship between SNS use and loneliness was mixed, with two studies finding no evidence for a simple association between SNS use and loneliness (Aarts, Peek and Wouters 2014;Bell et al 2013), and one study with an experimental design finding no change in loneliness following an SNS intervention (Myhre et al 2016). A qualitative study indicated that participants felt less lonely following an SNS intervention (Ballantyne et al 2010) and one study suggested that SNS use reduced the impact of functional disability on 'social' loneliness (frequency of social contact) (van Ingen, Rains and Wright 2017).…”
Section: What Is the Association Between Sns Use And Older Adults' Wementioning
confidence: 99%
“…Literature showed that when several barriers regarding social network sites (SNS) such as privacy, technical difficulties, and the fact that the majority of web designs do not yet consider the needs of older individuals were addressed, SNS could be considered a tool to support communication in older individuals . However, in a cross‐sectional study conducted in 2014, no relation between social media usage and loneliness was detected in community‐dwelling older adults . Hence, the primary purpose of this study was to examine what attitudes older adults have towards social media.…”
Section: The Four Themes That Arose From the Interviewsmentioning
confidence: 99%
“…Only persons who used social media were included. The interview guide, which was based on the available literature, ensured that the same set of topics was covered in all interviews: (1) attitudes regarding social media, (2) feelings related to social media, and (3) social media and well‐being. Recorded interviews were transcribed verbatim and analyzed by open and axial coding.…”
Section: The Four Themes That Arose From the Interviewsmentioning
confidence: 99%
“…Although there may be some people who benefit from new technology, there is equally serious concern that technology, if improperly used, may lead to higher rates of loneliness. More broadly, it may be too early to form conclusions on whether technology helps or hinders loneliness in older adults given the wide breadth of the type of technology use . It may be worth noting that older adults may actually need to worry more about their grandchildren's use of technology because there are alarming data on the use of technology and rising rates of loneliness in younger cohorts …”
Section: Epidemiologymentioning
confidence: 99%